"I Have a Kind of Power I Never Knew I Possessed" - Sean P. Connors (Study and Scrutiny, 2025)
Drawing on Foucault’s examination of the gaze as a disciplinary mechanism, and de Certeau’s discussion of how people use tactics to resist oppressive power systems, this article advocates reading the gaze in young adult dystopian fiction. To illustrate the complex readings that doing so makes possible, the author examines three young adult dystopias—M. T. Anderson’s Feed, Suzanne Collins’s Hunger Games trilogy, and Corey Doctorow’s Little Brother—to demonstrate how they depict adolescents as having varying degrees of agency to resist the gaze. To conclude, the author discusses the implications for teachers and students of reading the gaze in young adult literature.